Pengembangan Alat Edukatif Balok dan Puzzle Iqro’ untuk Mengenalkan Huruf Hijaiyah pada Santri Griya Qur’an Raudhatul Ilmi - Qoni’ah Al Munasiroh; M. Efrendi (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study focuses on the development of Iqro’ block and puzzle educational tools to introduce Hijaiyah letters to student’s at Griya Qur’an Raudhatul Ilmi. The research aims to determine the use of Iqro’ blocks and puzzle’s in teaching Hijaiyah letters, evaluate their effectiveness in enhancing children's recognition of these letters, and assess their practicality in the learning process. Using the Research and Development (R&D) method with the ADDIE model, this study comprises five stages: analysis, design, development, implementation, and evaluation. The results show that the Iqro’ blocks and puzzle significantly improve student’s ability to recognize Hijaiyah letters through interactive and enjoyable learning methods. The validation from experts indicated that the educational tool is highly feasible, achieving an average score of 4.76. Teachers also noted increased engagement and motivation among students during lessons utilizing the Iqro’ blocks and puzzle. This research underscores the importance of using innovative educational tools in early childhood education to enhance the learning experience and improve literacy skills.